2022
DOI: 10.1111/epi.17244
|View full text |Cite
|
Sign up to set email alerts
|

Limbic and paralimbic respiratory modulation: From inhibition to enhancement

Abstract: Objective: Increased understanding of the role of cortical structures in respiratory control may help the understanding of seizure-induced respiratory dysfunction that leads to sudden unexpected death in epilepsy (SUDEP). The aim of this study was to characterize respiratory responses to electrical stimulation (ES), including inhibition and enhancement of respiration. Methods:We prospectively recruited 19 consecutive patients with intractable epilepsy undergoing stereotactic electroencephalography (EEG) evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…These findings provide new insights into forebrain breathing modulation, and identify important nodes of a limbic/paralimbic breathing modulation network. These results identify, for the first time, amygdala, anterior insula, and thalamus as regions that increase MV, and support our previous observations of a similar role of anterior cingulate and temporal pole in breathing enhancement 15 . We found that such enhancement responses are dependent on specific stimulation paradigms, as previously suspected 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings provide new insights into forebrain breathing modulation, and identify important nodes of a limbic/paralimbic breathing modulation network. These results identify, for the first time, amygdala, anterior insula, and thalamus as regions that increase MV, and support our previous observations of a similar role of anterior cingulate and temporal pole in breathing enhancement 15 . We found that such enhancement responses are dependent on specific stimulation paradigms, as previously suspected 15 .…”
Section: Discussionsupporting
confidence: 92%
“…These results identify, for the first time, amygdala, anterior insula, and thalamus as regions that increase MV, and support our previous observations of a similar role of anterior cingulate and temporal pole in breathing enhancement 15 . We found that such enhancement responses are dependent on specific stimulation paradigms, as previously suspected 15 . In amygdala, we found that low‐frequency (<1 Hz) stimulation was associated with a 45.44% greater increase in MV compared to higher (≥10 Hz) frequencies.…”
Section: Discussionsupporting
confidence: 91%
“…Human studies have provided evidence for a role of the amygdala in seizure‐related apnea in PWE. Thus, spread of ictal activity to the amygdala is associated with the onset of apnea, and stimulation of the amygdala induces apnea in PWE 207–213 . These findings suggest a possible role of the amygdala in inducing apnea in SUDEP cases.…”
Section: Brain Structures Implicated In Sudepmentioning
confidence: 75%
“…Thus, spread of ictal activity to the amygdala is associated with the onset of apnea, and stimulation of the amygdala induces apnea in PWE. [207][208][209][210][211][212][213] These findings suggest a possible role of the amygdala in inducing apnea in SUDEP cases. However, seizure-related apneas were also reported to have an inconsistent linkage to amygdala seizure spread in a recent patient study.…”
Section: Amygdalamentioning
confidence: 79%
“…Possible therapeutic approaches could be based on electrical or optical stimulation of specific brain areas to "rebalance" their E/I activity and maintain cardiorespiratory function during and after seizures (198,236). Electrical stimulation in patients to map epileptic zones can inhibit or enhance respiration (237). Optogenetic neuronal activation has been shown to suppress seizure-induced respiratory arrest and exert an anticonvulsant effect in a SUDEP mouse model (238).…”
Section: Techniques To Study Network Interaction Involved In Sudepmentioning
confidence: 99%